Lutra longicaudis - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lutra longicaudis (Olfers, 1818). In Eschwege, Neue Bibl. Reisenb., 15(2):233. TYPE LOCALITY: Brazil. DISTRIBUTION: Mexico, Central America, W. South America south to Peru, E. South America south to Uruguay. COMMENT: Includes annectens, enudris, incaruni, and platensis; see Van Zyll de Jong, 1972, Life Sei. Contrib. R. Ont. Mus., 80:1 -104; Genoways and Jones, 1975, Occas. Pap. Mus. Texas Tech Univ., 26:1 -22. PROTECTED STATUS: CITES - Appendix I and U.S. ESA - Endangered as L. longicaudis. U.S. ESA - Endangered as L. platensis. ISIS NUMBER: 5301412004023003001 as Lontra longicaudis. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 258, DOI: 10.5281/zenodo.7352980